The Student Perspectives on the Effectiveness of Zoom Meeting Media in Increasing Knowledge of Thesis Writing at STKIP Muhammadiyah Manokwari - Ardian Eko Sajaril; Rahmatia Rahmatia; Syahira Syahira (International Journal of Education, Information Technology, and Others, 2020)
Every student has the right to get knowledge even during a Covid-19 pandemic like this. The knowledge can be obtained from any media including zoom meetings. However, the use of zoom meetings at STKIP Muhammadiyah Manokwari has not been effectively used, considering the many considerations that have become the basis for not using zoom meeting media on an ongoing basis. This study aims to determine the students' perceptions of the effectiveness of the Zoom meeting media in increasing thesis writing knowledge. This research uses a descriptive qualitative approach with the type of content analysis. Data obtained through a questionnaire distributed to students. The sample was taken by using a purposive sampling technique. The results showed that the use of zoom meeting media was not effective in increasing students' knowledge about thesis writing. There are two differences in the results of the questionnaire assessment. The questionnaire aspect contains the zoom meeting and student knowledge about research. Processed data shows that 70% of students say the zoom meeting media is effectively used and in the second questionnaire regarding the level of understanding of students in thesis writing, it shows that 60% of students experience an increase in knowledge. These results indicate the category of achievement of increasing student knowledge is less than the minimum effectiveness of 80%. In addition, this indicates that the results are inconsistent between the two components of the questionnaire so that it is said that the actual use of zoom meetings is not effective in increasing students' knowledge about thesis writing.